Two cases of freemartinism in Lacaune ewes - MENEGATOS (Ι. ΜΕΝΕΓΑΤΟΣ) J.; XYLOURI (Ε. ΞΥΛΟΥΡΗ) E.; AJOUTANTI (Α. ΑΓΙΟΥΤΑΝΤΗ) A.; SABATAKOU (Ο. ΣΑΜΠΑΤΑΚΟΥ) O.; PARASKEVAKOU (Ε. ΠΑΡΑΣΚΕΥΑΚΟΥ) E.; VAINAS (Ε. ΒΑΪΝΑΣ) E. (Journal of the Hellenic Veterinary Medical Society, 2017)
In this study the anatomy of the genital system, the histology of gonads, the reproductive behavior and the chromosome examinations of two freemartin Lacaune ewes were described. The appearance of these ewes resembled that of a ram, but their external genitalia were female with an enlarged clitoris. The gonads were small testicles located subcutaneously in the prepubic region. In the case of the ewel the testicles were palpated with difficulty, while in ewe 2 they were almost atrophic. In both cases there were epididymides, but in ewe 2 the ends of vasa differentia were joined. In ewel there were vesicular and bulbo-urethral glands. In ewe 2 the vesicular glands were absent. The ewel had male sexual behavior, but the ewe 2 had a neutral one. The histological examination of the gonads of ewe 1 showed excessive development of the vassoconnective tissue, where a small number of seminiferous tubules and Sertoli cells were also visible. The gonads of ewe 2 showed excessive fibrosis. The results of chromosome examination showed chimaerism (54,XX/XY) in both cases. The XY cells were 63% and 61% for the ewes 1 and 2, respectively. The rest cells 37% and 39% were respectively XX ones.